Effects of E.coli O157:H7 Experimental Infections on Rabbits: Donia Hatem Fadhel al-Taii and Afaf Abdulrahman Yousif - Yousif, Afaf Abdulrahman (The Iraqi Journal of Veterinary Medicine, 2019)
The study aimed to show the effect of experimental infection with E.coli O157:H7 on some liver and kidney function in adult rabbits. Twenty five domestic rabbits (males and females), aged 6-8 weeks and weighing 1500-2000g, had a negative fecal bacteriological culture of E.coli O157:H7 were used. The rabbits were randomly divided into two groups: infected group (15 rabbits), each animal was drenched orally with 1ml of Phosphate buffer saline containing (2×109CFU) of E.coli O157:H7, while the control group (10 rabbits) were drenched orally (1ml) of Phosphate buffer saline, the clinical signs were daily observed for 30 days, recording of body weight and blood samples were collected at (0, 3, 15 and 30) days for serum to evaluate biochemical tests including Alanine transaminase, Aspartate aminotransaminase and alkaline phosphatase, creatinine, urea and total serum protein. The results showed different clinical signs after inoculation, including diarrhea, lethargy, weight loss, inability to eat or drink, urine was cloudy or milky, while control group remains in normal condition. The serum biochemical tests in infected group showed a significant increase of three enzymes at 15, and 30 days, the highest values of Alanine transaminase; Aspartate aminotransaminase and alkaline phosphatase showed at 30 days post infection as compared with the control group. Serum creatinine and urea recorded a significant increase (P< 0.05) at 30 day post infection as compared with control group. However, total protein revealed a significant decrease in the infected group, and a significant decrease was noticed at 15 day post infection, while the control group showed an increase in total protein co-ordinated with increase of body weight and progressing age. This study concluded that the infection with E. coli O157:H7may cause changes in liver and kidney functions which were more sever at 15,30 days post infection.